Psychometric properties of the Modified Breast Cancer Screening Beliefs Questionnaire among Mainland Chinese women. (June 2017) - Bao, Yingyi; Kwok, Cannas; Lee, Chun Fan
Abstract: Purpose: The aim of the study was to report the psychometric properties of the modified 'Breast Cancer Screening Beliefs Questionnaire' (BCSBQ) among women living in China. Methods: A convenience sample of 494 women was recruited from community centres and out-patient clinics in Foshan city. Cronbach's alpha was used to assess internal consistency reliability. Criterion validity was examined by testing three pre-specified hypotheses and confirmatory factor analysis was conducted to study the factor structure. Results: The results indicated that the modified BCSBQ has satisfactory validity and internal consistency. Cronbach's alpha of the three subscales ranged between 0.77 and 0.84. As hypothesized, the frequencies of breast self-examination and clinical breast examination were significantly associated with the subscales' score. Confirmatory factor analysis showed an adequate fit for the hypothesized three-factor structure with our data set. Conclusions: The modified BCBSQ is a culturally appropriate, valid and reliable instrument for assessing the beliefs, knowledge and attitudes to breast cancer and breast cancer screening practices among women living in China. It can be used for providing health care professionals with insights into the development of breast cancer screening promotion programs. Highlights: Little is known about breast cancer screening behaviours among Chinese women in Mainland China. Valid and reliable instrument is essential to understand factors that influence Chinese women's breast cancer screening behaviours. The Modified Breast Cancer Screening Beliefs Questionnaire is a culturally appropriate, valid and reliable instrument for assessing the beliefs, knowledge and attitudes to breast cancer and breast cancer screening practices among Chinese women in Mainland China.